2016
DOI: 10.1016/j.cherd.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics study of the modified rotating disc contactor for CO2 absorption from natural gas using emulsion liquid membrane

Abstract: A c c e p t e d M a n u s c r i p t Highlights:Emulsion liquid membrane in rotating disc contactor was used for CO2/CH4 separation A stable emulsion liquid membrane was formulated by high-speed homogenization The characteristics of emulsion liquid membrane system were evaluated The process parameters for CO 2 separation from natural gas were analyzed ABSTRACT This study modified the rotating disc contactor (RDC) structure to optimize its performance for CO 2 separation from natural gas feed using stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…Based on Figure 1, the stability of emulsion was at lowest which at 9.6% when DOPC acted as the only surfactant for sample 3. This finding agreed with paper published by Kim et al, where the researcher reported that DOPC is typically unstable because of its molecular structure whose HLB value is moderate (7), therefore resulting in the poor stability of W/O emulsion [6].…”
Section: Figure 1: the Stability Of Emulsion Using Different Formulationsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on Figure 1, the stability of emulsion was at lowest which at 9.6% when DOPC acted as the only surfactant for sample 3. This finding agreed with paper published by Kim et al, where the researcher reported that DOPC is typically unstable because of its molecular structure whose HLB value is moderate (7), therefore resulting in the poor stability of W/O emulsion [6].…”
Section: Figure 1: the Stability Of Emulsion Using Different Formulationsupporting
confidence: 92%
“…Two different types of aqueous phase were used, there were the combination of MDEA/AMP and MDEA only. For MDEA/AMP, 8% v/v MDEA and 88% NaOH and 4% v/v AMP and for MDEA, 8% v/v MDEA was the best for CO2 absorption [7]. Despite the appealing features of emulsion, this technique used in absorption is not widespread used due to the instability of emulsion [8].…”
Section: The Effect Of Cosurfactant In Co2 Absorption In Water -In -Omentioning
confidence: 99%
See 1 more Smart Citation